¿Si esto no es el pueblo, el pueblo dónde está? Discursive Disagreement in the 2019-2020 Post-electoral Conflict in Bolivia - Jonathan Alderman (Bolivian Studies Journal)
The 2019 electoral crisis in Bolivia was characterized by division and disagreement. In the three weeks between the country’s presidential election in October 2019 and sitting President Evo Morales’s resignation, both Morales’s supporters and his detractors marched in the streets chanting parallel slogans in which each identified themselves as “the people” (el pueblo).  This article examines what it means to identify collectively as “the people” in contemporary Bolivia and the nature of the term as a floating signifier used to justify   opposing   claims  by  protestors  on  both  sides  of defending Bolivian democracy. The use of the same self-identification by different groups represents a disagreement of the kind referred to by Jacques Rancière when two actors use the same term without recognizing the meaning given to it by the other. This disagreement is representative of competing ideas about democracy, belonging and the nation itself operating simultaneously within Bolivia.